Pengaruh Sarana Prasarana dan Mutu Layanan Pendidikan terhadap Kepuasan Siswa Madrasah Tsanawiyah se-Kota Blitar - Nauraida, Indah Dwi; Sobri, Ahmad Yusuf; Sultoni, Sultoni (JAMP : Jurnal Administrasi dan Manajemen Pendidikan, 2024)
Abstract: This study aims to conduct an in-depth analysis of the impact of facilities, infrastructure, and the quality of educational services on student satisfaction in educational institutions. The research uses a quantitative approach with a correlational method. The population of the study consists of 3,018 students from madrasah tsanawiyah in Blitar City. The sample was obtained using proportional random sampling, resulting in a sample of 353 students. Data analysis was performed using descriptive analysis techniques and multiple linear regression analysis. The results of the study show: (1) the level of facilities and infrastructure at madrasah tsanawiyah in Blitar City is categorized as good; (2) the quality of educational services at madrasah tsanawiyah in Blitar City is categorized as good; (3) the level of student satisfaction at madrasah tsanawiyah in Blitar City is categorized as good; (4) there is a significant influence of facilities and infrastructure on the satisfaction of students at madrasah tsanawiyah in Blitar City; (5) there is a significant influence of the quality of educational services on the satisfaction of students at madrasah tsanawiyah in Blitar City; and (6) there is a significant and simultaneous influence of facilities, infrastructure, and the quality of educational services on the satisfaction of students at madrasah tsanawiyah in Blitar City. Keywords: infrastructure, quality of educational services, student satisfaction Abstrak: Penelitian ini bertujuan untuk menganalisis secara mendalam pengaruh sarana dan prasarana serta mutu layanan pendidikan terhadap kepuasan siswa di lembaga pendidikan. Penelitian ini menggunakan pendekatan kuantitatif dengan metode korelasional. Populasi dalam penelitian adalah siswa madrasah tsanawiyah se-Kota Blitar dengan jumlah populasi 3018 siswa. Pengambilan sampel penelitian ini yaitu menggunakan proportional random sampling dan diperoleh sampel penelitian sebanyak 353 siswa. Analisis data menggunakan teknik analisis deskriptif dan analisis regresi linear berganda. Hasil penelitian menunjukkan: (1) tingkat sarana dan prasarana di madrasah tsanawiyah se-Kota Blitar termasuk dalam kategori baik; (2) tingkat mutu layanan pendidikan di madrasah tsanawiyah se-Kota Blitar termasuk dalam kategori baik; (3) tingkat kepuasan siswa di madrasah tsanawiyah se-Kota Blitar termasuk dalam kategori baik; (4) terdapat pengaruh yang signifikan antara sarana prasarana dengan kepuasan siswa madrasah tsanawiyah se-Kota Blitar; (5) terdapat pengaruh yang signifikan antara mutu layanan pendidikan dengan kepuasan siswa madrasah tsanawiyah se-Kota Blitar; dan (6) terdapat pengaruh yang signifikan dan simultan antara sarana prasarana dan mutu layanan pendidikan dengan kepuasan siswa madrasah tsanawiyah se-Kota Blitar. Kata kunci: sarana prasarana, mutu layanan pendidikan, kepuasan siswa